PENGARUH PENERAPAN METODE BRAINSTORMING TERHADAP KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 13 PALEMBANG - Yuliani Kartika Putri; Muhammad Djahir Basir; Ikbal Barlian (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2016)
Abstract: This study aims to determine whether there are differences in methods of brainstorming with quatum method of learning to students' learning activeness on economic subjects in SMAN 13 Palembang. The population in this study were students of class X MIA in SMAN 13 Palembang which consists of 6 classes totaling 243 students. The research sample using random cluster sampling, so that the selected class X MIA 1 totaling 40 students as an experimental class and class X MIA 2 totaling 40 students as the control class. Data collection techniques such as observation aims to determine the application of methods of brainstorming with quatum method of learning to students' learning activeness, while the questionnaire is used as supportive data from the observation, questionnaire given at the last meeting. The data analysis technique used to test the hypothesis using t-test was obtained thitung 3,69 ? ttabel 1,98. Based on the results of this study concluded that there are differences in the effect of applying methods of brainstorming with quatum method of learning to students' learning activeness with the results of experimental observation average grade 83.63% with a good category while the average grade control 69.70% with a category quite well while the results of the questionnaire average class experiment 51.45% while the average of 49.8% of control class questionnaire. Based on the conclusion, it is suggested for further research in order to pay attention to the obstacles in this research that when the focus groups did not refer to the students' learning activeness.Abstrak: Penelitian ini bertujuan untuk mengetahui apakah ada perbedaan metode brainstorming dengan metode quatum learning terhadap keaktifan belajar siswa pada mata pelajaran ekonomi di SMA Negeri 13Palembang. Populasi dalam penelitian ini adalah siswa kelas X MIA di SMA Negri 13 palembang yang terdiri dari 6 kelas yang berjumlah 243 siswa. Sampel penelitian menggunakan cluster random sampling, sehingga terpilih kelas X MIA 1 yang berjumlah 40 siswa sebagai kelas eksperimen dan kelas X MIA 2 yang berjumlah 40 siswa sebagai kelas kontrol. Teknik pengumpulan data berupa observasi bertujuan untuk mengetahui penerapan metode brainstorming dengan metode quatum learning terhadap keaktifan belajar siswa, sedangkan angket digunakan sebagai data pendukung dari hasil observasi, angket diberikan pada saat pertemuan terakhir. Teknik anaslis data yang digunakan untuk menguji hipotesis dengan uji-t di peroleh thitung sebesar 3,69 ? ttabel1,98. Bedasarkan hasil penelitian dapat disimpulkan bahwa terdapat perbedaan pengaruh penerapan metode brainstorming dengan metode quatum learning terhadap keaktifan belajar siswa dengan hasil obsevasi rerata kelas eksperimen 83,63% dengan kategori baik sedangkan rerata kelas kontrol 69,70% dengan kategori cukup baik sedangkan hasil rerata angket kelas eksperimen 51,45% sedangkan rerata angket kelas kontrol 49,8%. Bedasarkan simpulan, disarankan bagi peneliti selanjutnya agar dapat memperhatikan hambatan dalam penelitian ini yaitu ketika hasil angket yang tidak merujuk pada keaktifan belajar siswa